WACANA PUBLIK DIGITAL DAN PEMETAAN KEBIJAKAN - Gita Nindya Elsitra; Wijayanto - - (Journal of Politic and Government Studies, 2021)
When digital technology in Indonesia rapidly develops, and the government stimulates that furthermore, children become more vulnerable in their cyber activities. Therefore, this research appears to highlight children’s cyber safety in Semarang City. There are two research questions: how is children’s cyber problematic activities and children’s cyber safety policy. To answer those questions, the researcher uses a qualitative method by interviewing primer sectors related to the issues and doing discourse analysis in digital media. By focusing the issues into some crucial problematic activities, the researcher found out that Semarang City’s digital public discourse is revolving in the matter of children’s internet addiction. Which means, also related to the other problematic issue: online child pornography and cyber-bullying.